YUDISIALISASI DAN LIMITASI HUKUM ISLAM: CERAI TALAK DI PENGADILAN AGAMA DI LOMBOK - Nasir, Mohamad Abdun; Sunardi, Heru (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
Male repudiation (cerai talak) at religious courts reveals important changes in contemporary practice of Islamic law in Indonesia. This paper addresses two salient features of repudiation, namely judicialization and limitation. Based on empirical studies at the religious courts in Lombok, this study gathered the data on repudiation through observation, interview and documentation. The data shows changing practice and meaning of Islamic marital dissolution due to judicialization, that is an administrative and bureaucratic processes of legal settlement at religious courts. Upon the introduction and application of modern codification of Islamic law, such as the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) enacted by Presidential Decree No. 1/1991 and Religious Judicature Act No. 7/1989 at religious courts, the influence of fiqh on Islamic divorce has diminished significantly. Such application not only creates judicialization but also causes limitation on the number of male repudiation, outnumbered by female-initiated divorce (cerai gugat). Talak, which is male domain under the conception of fiqh, is now a contested terrain by legal actors, such as men (husbands), women (wives) and judges. Consequently, judicialization of talak has reduced not only male power but also its practice at the religious courts.Cerai talak di pengadilan agama mencerminkan perubahan-perubahan penting dalam penerapan hukum Islam kontemporer di Indonesia. Artikel ini membahas dua fenomena mengemuka praktik talak, yaitu yudisialisasi dan limitasi. Berangkat dari penelitian empiris di pengadilan agama di Lombok dengan metode pengumpulan data melalui observasi, wawancara dan dokumentasi, penelitian ini meyingkap pergeseran pemaknaan dan praktik talak kontemporer. Hal ini disebabkan oleh yudisialisasi, yaitu proses administrasi dan birokratiasasi penyelesaian perkara di pengadilan agama. Pasca diperkenalkannya kodifikasi hukum keluarga Islam, seperti Kompilasi Hukum Islam melalui Instruksi Presiden No. 1/1991 maupun Undang-undang Peradilan Agama No. 7/1989, pengaruh fikih dalam hukum perceraian Islam berkurang secara signifikan seiring dengan pemberlakuan kodifikasi di pengadilan agama. Implikasinya bukan saja pada yudisialisasi, akan tetapi juga limitasi talak, yakni terbatasnya perkara cerai talak dibanding cerai gugat. Talak yang dalam norma fikih menjadi domain kuasa suami yang hampir mutlak, kini dalam praktiknya di pengadilan agama menjadi wilayah yang dikontestasikan oleh para aktor hukum, baik suami, istri maupun hakim sehingga berdampak pada limitasi talak, baik dari segi kuantitas perkara maupun kuasa suami dalam penyelesaian cerai talak.